Oral Administration of Paneeya Kshara (Alkaline Preparations) and its Role in the Management of Mutrashmari (Renal Calculi)- A Critical Appraisal (AYUSHDHARA, 2022)
Renal calculi are defined as the crystalline mineral deposits that are formed in the kidney. It has a global prevalence 15%. These stones are formed when the urine becomes excessively supersaturated with respect to a mineral, leading to crystal formation, growth, aggregation and retention within the kidneys that develop in the urinary tract and are known as Nephrolithiasis or Urolithiasis. Though multiple and advanced treatments are available to treat the renal stones, complete relief and non recurrence is still not possible. In Ayurvedic science, renal stones or the urolithiasis can be correlated to Mutrashmari, which is said to be a disease of Mutravaha srotas. Though various types of treatments are available in the classics, the unique oral medication known as Paneeya kshara or the oral medication prepared out of alkaline substances is described by Acharya Susrutha in Sushrutha samhitha for the successful management of Mutrashmari. In Ayurveda, many types of Paneeya kshara have been found that has been described for the management of Mutrashmari and many studies has been conducted on the same. In the present study, an attempt has been made to review all such studies that have evaluated the different types of Paneeya kshara in the treatment of Mutrashmari were systematically reviewed to put the best possible inputs into this study so that it helps the future researcher in conducting further studies on the disease and the intervention.